Development of a novel SupraChoroidal-to-Optic-NervE (SCONE) drug delivery system - Bryce Chiang; Kathleen Heng; Kyeongwoo Jang; Roopa Dalal; Yaping Joyce Liao; David Myung; Jeffrey L Goldberg (Drug Delivery)
Purpose Targeted drug delivery to the optic nerve head may be useful in the preclinical study and later clinical management of optic neuropathies, however, there are no FDA-approved drug delivery systems to achieve this. The purpose of this work was to develop an optic nerve head drug delivery technique.Methods Different strategies to approach the optic nerve head were investigated, including standard intravitreal and retroorbital injections. A novel SupraChoroidal-to-Optic-NervE (SCONE) delivery was optimized by creating a sclerotomy and introducing a catheter into the suprachoroidal space. Under direct visualization, the catheter was guided to the optic nerve head. India ink was injected. The suprachoroidal approach was performed in New Zealand White rabbit eyes in vivo (25 animals total). Parameters, including microneedle size and design, catheter design, and catheter tip angle, were optimized ex vivo and in vivo.Results Out of the candidate optic nerve head approaches, intravitreal, retroorbital, and suprachoroidal approaches were able to localize India ink to within 2 mm of the optic nerve. The suprachoroidal approach was further investigated, and after optimization, was able to deposit India ink directly within the optic nerve head in up to 80% of attempts. In eyes with successful SCONE delivery, latency and amplitude of visual evoked potentials was not different than the naïve untreated eye.Conclusions SCONE delivery can be used for targeted drug delivery to the optic nerve head of rabbits without measurable toxicity measured anatomically or functionally. Successful development of this system may yield novel opportunities to study optic nerve head-specific drug delivery in animal models, and paradigm-shifting management strategies for treating optic neuropathies.Translational Relevance Here we demonstrate data on a new method for targeted delivery to the optic nerve head, addressing a significant unmet need in therapeutics for optic neuropathies.